ATOPIC DERMATITIS IN CHILDREN AND ANTIBODIES TO STAHPYLOCOCCUS AUREUS SUPERANTIGENS: A COMPARISON WITH SUSCEPTIBILITY TO ANTIBIOTICS - M. S. Treneva; A. N. Pampura; T. S. Okuneva (Педиатрическая фармакология, 2012)
Background. Staphylococcus aureus function in atopic dermatitis (AD) children skin is double-handed: an infectious trigger and an allergen. The aim of the study was to evaluate the frequency of S. aureus enterotoxins the IgE in children with infected AD skin and to compare the IgE levels with antibiotic resistance of S. aureus. Methods: specific IgE to S. aureus enterotoxins A and B (ImmunoCap, Phadia AB, Sweden) were detected in the serum of 90 children infected with AD. The IgE levels were compared with the resistance to antibiotics (McNemar test and 95% confidential intervals of related frequencies). Results: specific IgE > 0,35 kUA/l to S. aureus enterotoxin A were found with a frequency of 0,29; to enterotoxin B — 0,36; to at least one of them — 0,43. The number of children with IgE > 0,35 kUA/l and S. aureus resistant to antibiotics was about 1/3 of the number of children with IgE < 0,35 kUA/l and S. aureus sensitive to antibiotics (р < 0,001). S. aureus in children with IgE > 0,35 kUA/l remained sensitive to oxacillin. Conclusion. In children infected with AD S. aureus enterotoxins A or/and B are revealed in 25–50% of cases. Specific IgE levels to S. aureus enterotoxins are similar in antibiotic resistant and antibiotic sensitive S. aureus skin swabs — about 30%. The IgE level to enterotoxins of S. aureus and its antibiotic resistance don't seem to be conditioned by each other.